PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING (STUDI PADA POLITEKNIK ILMU PELAYARAN (PIP) SEMARANG) - Romanda Annas Amrullah (Jurnal Bisnis dan Ekonomi, 2014)
Performance is a factor that supports the organization's effectiveness and performance based on the ability of managers to carry out managerial duties. This performance will be optimal if the managers involved in the budgeting process must have been influenced by the organizational culture and commitment held by existing employees within the organization. The managers who are involved in the budgeting process managers can determine how much of its ability to achieve the targets to be achieved so that raises confidence in the manager.The purpose of this study was to analyze the effect of budget participation on managerial performance. To analyze the influence of organizational culture and organizational commitment moderated the budget participation on managerial performance. Types of research used in this study using explanatory research methods. The population in this research is the head of affairs, and chairman of the department head unit, amounting Semarang Merchant Marine Polytechnic to 34 respondents. The sampling technique used in this study is the census. Analysis tool used is multiple linear regression. Based on this study concluded: There is a positive and significant effect between budget participation on managerial performance, organizational culture moderates the positive and significant effect between budget participation on managerial performance, organizational commitment moderates the positive and significant effect between budget participation on managerial performance, Keywords: Participation Budgeting, Managerial Performance, Organizational Culture, Organizational Commitment